MAIN APPROACHES TO EFFICACY EVALUATION OF SPECIALIZED PRODUCTS FOR PREGNANT WOMEN - I.Ya. Kon'; M.V. Gmoshinskaya; E.Yu. Demkina (Вопросы современной педиатрии)
Use of specialized products is one of the ways of improving pregnant women nutrition. Efficacy evaluation is done by unification method,  that is based on product tolerance study, their influence progress and outcome of the pregnancy, foetus and women’s nutritive status.  This article contains guidelines of clinical physiological evaluation of efficacy of specialized products for pregnant women. Inclusion and exclusion criteria as well as efficacy variables are also included in the article.Key words: pregnant women, specialized products. (Voprosy sovremennoi pediatrii — Current Pediatrics. — 2011; 10 (6): 119–121.)